Graduates Skills Developments for Libyan Labour Market - Edali, Mohamed; Alaswad, Walid; Milad, Asma; Bseibsu, Ali; Alajaili, Tareq; Sahem, Zaed; Ben Rajeb, Faraj; Elkamel, Ali (International Journal of Engineering Research, 2023)
Any educational program's outcomes can be described in terms of both knowledge and skills. Chemical engineering graduates' skills and abilities might include those unique to managing material and energy balances and problem-solving skills that are generic or transferrable. This paper is concerned mainly with personal or transferable skills. It is widely acknowledged that one of the most critical abilities for chemical engineering graduates is the ability to communicate well in several written and spoken formats. The ability to work effectively in groups; be proactive and initiative in problem-solving; be numerate and IT literate; and ability to manage oneself and continue to learn are all desirable qualities. In some particular instances, it is illustrated that within our chemical engineering programme at Elmergib University, there are various and different chances to acquire these abilities in order to satisfy the demands of Libyan industries. This research considers how transferable skills can be defined and prioritized and then developed within the chemical engineering curriculum. A systematic strategy was designed to determine where and how skills can be managed and integrated into the curriculum. Chemical engineering graduates from Elmergib University were solely satisfied with their decision to pursue a degree in the field.